Haemodynamic effects of hydralazine at rest and during exercise in patients with chronic heart failure. Issue 3 (September 1980) - Ginks, W R; Redwood, D R
Abstract : The administration of vasodilator drugs has been shown to have beneficial effects at rest in patients with acute or chronic heart failure. To determine the efficacy of hydralazine during exercise, 10 severely symptomatic patients with chronic left ventricular failure from diffuse coronary disease or cardiomyopathy were studied at rest and during upright exercise on a bicycle ergometer. All patients were already receiving optimal treatment with digitalis and diuretics. At rest treatment with hydralazine resulted in a fall in both mean arterial and pulmonary wedge pressure. There was a 50 per cent reduction in systemic vascular resistance compared with pretreatment measurements and there was an equally impressive increase in stroke volume index. During exertion the changes noted at rest were sustained though occurred to a lesser degree; thus there was a 20 per cent fall in arterial resistance and a 20 per cent rise in stroke volume index compared with control. These findings show that hydralazine administration not only results in a beneficial effect on cardiac function at rest but that this effect is maintained during upright exercise in patients with impaired left ventricular function, thus providing further support for its use in the long-term management of such patients.